Pengaruh Online Marketing, Simpati, Dan Inovasi Brand Terhadap Keputusan Pembelian di Warung ATK Purnima - Hendry, Raja Saul Marto (Jurnal Manajemen Akuntansi (JUMSI), 2023)
The ATK industry is one of the fastest growing sectors, including one of the emerging stores in Rantauprapat, Warung ATK Purnima. Warung ATK Purnima is present as one of the major players in providing various ATK products. In an increasingly competitive context, factors such as online marketing, sympathy, and brand innovation play a crucial role in shaping consumer purchasing decisions. ATK industry is a sector that continues to grow and has an important role in meeting the aesthetic and personal care needs of the community. Demand for ATK products continues to increase along with increased consumer awareness of the appearance and health of the skin. By providing a variety of quality ATK products, this store has managed to attract the attention of consumers and build a positive image. Warung ATK Purnima is famous for its emphasis on product innovation. Through careful research and development, the store is always introducing new and high-quality products, in line with the latest ATK trends. By creating a comfortable, friendly and interactive shopping environment, the store has managed to build good relationships with customers, create loyalty and support the growth of its business.